Editorial: sofosbuvir plus daclatasvir for the treatment of hepatitis C—can one size fit all?. Issue 6 (15th February 2018) - Sun, J.; Liang, X.; Fan, R.; Hou, J.
Linked content: This article is linked to El‐Khayat et al paper. To view this article visit https://doi.org/10.1111/apt.14482 .